ANALISIS STRATEGI BANK INDONESIA MEMPERTAHANKAN BI-RATE DI TENGAH DEPRESIASI RUPIAH KUARTAL I/2026 - Nayla Al Afifah; Aldila Krisnaresanti; Dian Isnawati (Bajang Institute, 2026)
Entering the first quarter of 2026 (Q1/2026), the Indonesian economy was faced with escalating global uncertainty, triggering significant depreciation pressure on the Rupiah exchange rate. In confronting this external shock, Bank Indonesia (BI) was presented with a crucial macroeconomic dilemma between raising the benchmark interest rate to curb capital outflow or maintaining it to preserve the recovery momentum of the domestic real sector. We aim to dissect Bank Indonesia's strategy and policy foundation in maintaining the BI-Rate amidst the weakening trend of the Rupiah throughout Q1/2026. Specifically, this paper evaluates the effectiveness of non-interest rate policy mix—such as the optimization of Bank Indonesia Rupiah Securities (SRBI) and dual intervention in the foreign exchange market—as substitute instruments for monetary tightening. This study employs a qualitative descriptive-analytical approach with an evaluative case study method. The data utilized consists of secondary, real-time data from Q1/2026 obtained from the official reports of Bank Indonesia's Board of Governors' Meeting (RDG). The policy analysis is conducted through a chronological comparative method, utilizing empirical baselines from the first quarter of 2020–2024 monetary transitions and the 2025 policy responses